PESANTREN AS COUNTER-HEGEMONIC INSTITUTIONS CHALLENGING SDGs TOWARD INDONESIA EMAS 2045 - Fadillah, M. Kharis; Fitriani, Namiyah; Asy-Syahidah, Qorina Himmati (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2026)
This study examines the repositioning of pesantren in supporting the achievement of Sustainable Development Goals (SDGs), particularly quality education as a strategic pathway toward Indonesia Emas 2045. As value-based Islamic educational institutions, pesantren have strong potential in character building, competency development, and community empowerment. However, their role in sustainable development remains insufficiently integrated into policy and educational practice. This research employs a qualitative conceptual approach based on library research. Data were collected from academic literature, international reports, and national policy documents, and analyzed using thematic and integrative methods. The findings reveal that the repositioning of pesantren can be achieved through the integration of value-based education, 21st-century competencies, and community empowerment. This integration results in the Pesantren-Based Sustainable Education Model, positioning pesantren as strategic actors in education and sustainable development. This study contributes both theoretically and practically to optimizing the role of pesantren toward Indonesia Emas 2045, while also providing insights for policymakers and educators.